Pengaruh Model Discovery Learning terhadap Hasil Belajar Peserta Didik di SMP Negeri 1 Alasa - Enjel Otniat Putri Harefa; Kensi Agnes Sofyanti Lahagu; Agnes Renostini Harefa (Departement of Mathematics Education, 2023)
This research was conducted to see how the Discovery Learning learning model affects student learning outcomes at SMP Negeri 1 Alasa. This study used a real experiment with a pretest-posttest control group design. All participants in this study were grade VIII SMP Negeri 1 Alasa. The direct random sampling process was used to select samples, and class VIII-1 was designated as the experimental class and class VIII-2 as the control class. In this study, the test instrument consisted of 20 multiple choice questions. With SPPS, data analysis uses t-test. Based on the results of the independent sample t-test which gives a significance value of 0.000 > 0.05, the hypothesis can be accepted that the discovery learning model influences student learning outcomes at SMP Negeri 1 Alasa.